2012
DOI: 10.1021/pr3002244
|View full text |Cite
|
Sign up to set email alerts
|

LuxS-Dependent AI-2 Regulates Versatile Functions in Enterococcus faecalis V583

Abstract: Bacteria utilize a quorum sensing (QS) system to coordinate gene expression by monitoring the concentration of molecules known as autoinducers (AI). In the present study, we confirmed the presence of a LuxS/AI-2 dependent QS system in vancomycin-resistant Enterococcus faecalis V583. Then, the cellular targets controlled by AI-2 were identified by comparative proteomics analysis in order to elucidate the possible role of AI-2 in E. faecalis. Results demonstrated 15 proteins that are differentially expressed upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 71 publications
3
26
0
1
Order By: Relevance
“…faecalis , like other Gram-positive and Gram-negative bacteria, the LuxS enzyme is involved in the transcriptional regulation of a series of genes, including those involved in ATP generation, translation, cell wall/membrane biogenesis, and nucleotide transport and metabolism [10]. However, the mechanisms that induce the deregulation of genes implicated in these pathways, remain unclear.…”
Section: Luxs Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…faecalis , like other Gram-positive and Gram-negative bacteria, the LuxS enzyme is involved in the transcriptional regulation of a series of genes, including those involved in ATP generation, translation, cell wall/membrane biogenesis, and nucleotide transport and metabolism [10]. However, the mechanisms that induce the deregulation of genes implicated in these pathways, remain unclear.…”
Section: Luxs Systemmentioning
confidence: 99%
“…With the advent of proteomic studies in bacteria, it is revealed that the quorum-sensing system not only regulates their specific regulon but also control the expression of many other proteins ranging from surface proteins, transcription factors, virulence, biofilm formation to metabolic pathways [9,10,11]. Proteomics allow a comprehensive understanding of quorum-sensing phenomena and make it possible to better discern patterns of proteins expression in bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the elucidation of the molecular circuits affiliated with AI-2 is an ongoing investigation, the role of AI-2 signaling molecules in biofilm formation and maturation has been unequivocally demonstrated in a variety of pathogens. The list includes the nontypeable Haemophilus influenzae [69], Campylobacter jejuni [70], A. actinomycetemcomitans [71], E. faecalis [72], Aeromonas hydrophila [73], V. cholerae [74] and Klebsiella pneumoniae [75]. …”
Section: Biofilmsmentioning
confidence: 99%